2015
DOI: 10.1245/s10434-015-4558-4
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Skeletal Muscle Mass During Neoadjuvant Chemoradiotherapy Predicts Postoperative Mortality in Esophageal Cancer Surgery

Abstract: BackgroundEsophageal surgery is associated with complications and mortality. It is highly important to develop tools predicting unfavorable postoperative outcome. Esophageal cancer and neoadjuvant chemoradiotherapy (CRT) induce skeletal muscle wasting, which leads to diminished physiologic reserves. The purpose of this study was to investigate whether the degree of muscle mass lost during neoadjuvant CRT predicts postoperative mortality.MethodsA total of 123 consecutive patients undergoing surgery for esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
120
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 30 publications
9
120
1
Order By: Relevance
“…In another study, sarcopenia was present in 56 and 67% of patients before and after neoadjuvant chemoradiotherapy, respectively. This decrease in muscle mass was predictive of postoperative mortality in the stage III-IV subgroup of patients [99]. Furthermore, most of the radiotherapy-related toxicities are strongly associated with patient's nutritional status.…”
Section: Nutrition Issues During Chemotherapy and Radiotherapymentioning
confidence: 89%
“…In another study, sarcopenia was present in 56 and 67% of patients before and after neoadjuvant chemoradiotherapy, respectively. This decrease in muscle mass was predictive of postoperative mortality in the stage III-IV subgroup of patients [99]. Furthermore, most of the radiotherapy-related toxicities are strongly associated with patient's nutritional status.…”
Section: Nutrition Issues During Chemotherapy and Radiotherapymentioning
confidence: 89%
“…1423 However, definition of sarcopenia and means of the measurement of SM area varied among studies. Peng et al defined sarcopenia as a group of the patients in the lowest sex-specific quartile of the total psoas muscle index in the population, and showed that sarcopenia was associated with 3-year mortality after surgery for PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…1113 Sarcopenia can be objectively evaluated using a single slice of abdominal CT, and has increasingly been reported to be associated with poor survival or postoperative complications among various types of cancer patients. 1423 …”
Section: Introductionmentioning
confidence: 99%
“…However, Ida et al [22] reported that changes in some body component parameters, including skeletal muscle, during NACT were correlated with the occurrence of postoperative complications. Reisinger et al [23] found that loss of muscle mass during neoadjuvant chemoradiotherapy was associated with postoperative mortality in patients with stage III-IV esophageal cancer. They speculated that more advanced tumors may increase the resting energy expenditure of the host, and patients with stage III or IV disease may be more prone to loss of muscle mass.…”
Section: Discussionmentioning
confidence: 99%